Effects of the Remaining and/or Spontaneously Regenerated Facial Axons After Hypoglossal–Facial Nerve Neurorrhaphy for Facial Paralysis - Zhuang, Yuan; Ling, Miao; Li, Zhen; Li, Dezhi; Wan, Hong; Schumacher, Michael; Liu, Song (Frontiers in Neurology, 2020)
Background The incidence of incomplete facial paralysis is now relatively higher in clinical practice, and surgical intervention is still desirable for patients with significant facial paralysis. However, the importance and usefulness of the remaining and/or spontaneously regenerated facial axons for regaining facial function when using hypoglossal-facial nerve (HN-FN) neurorrhaphy or other nerve transferring methods to treat facial paralysis remain controversial. Objective We designed a rat FN injury model with preservation of the anatomical structure followed by HN-FN side-to-side neurorrhaphy to investigate the effects of the remaining and/or spontaneously regenerated FN axons on restoration of facial function. Methods After the evident return of facial function in three months following FN injury and HN-FN side-to-side neurorrhaphy, the FN was cross-sectioned again according to different ratios (0%, 30%, 70% and 100%) at the site rostral to the initial FN injury to retain, partially abolish or completely abolish the spontaneously regenerated FN axons that had successfully reinnervated the paralyzed facial muscles. Then, FN function was assessed using clinical evaluation methods and electrophysiological examinations, as well as retrograde labeling and axonal counting assessments of the reconstructed nerve pathways. Results The evaluations show that the remaining facial axons not only influenced the extent of regained function, such as facial symmetry, eye blinking activity and vibrissae motion, but also had an impact on regeneration and innervation of hypoglossal motoneurons. Conclusion Participation of remaining or spontaneously regenerated facial axons plays an important role in innervating paralyzed facial muscles by both facial and hypoglossal motoneurons, thus reestablishing facial function.